Assembly of glycoamino acid building blocks: a new strategy for the straightforward synthesis of heparan sulfate mimics12. Issue 95 (15th November 2018) - Revuelta, Julia; Fuentes, Roberto; Lagartera, Laura; Hernáiz, María José; Bastida, Agatha; García-Junceda, Eduardo; Fernández-Mayoralas, Alfonso
Abstract : We report on a new class of linear heparan sulfate mimics prepared by the assembly of glycoaminoacid building blocks. Abstract : A new strategy that enables a modular straightforward synthesis of heparan sulfate oligosaccharide mimics by the assembly of simple glycoamino acid building blocks is described. The coupling between units is readily carried out by an amidation reaction. Several glycoamino acid oligomers were prepared and their interaction with the FGF2 protein was analyzed.